Relationship between Teacher Professional Performance and Discipline of Workers with Teacher Professionalism in Madrasah Tsanawiyah in Pematangsiantar City - Mardianto; Kalsum Saragih (Britain International for Academic Research (BIAR) Publisher, 2019)
This study aims to determine: 1) the relationship between professional money teachers with professional teachers in MTs Pematangsiantar, 2) the relationship between the discipline of working with the professionalism of teachers in MTs Pematangsiantar, and 3) the relationship between the Advantages of the teaching profession and discipline of cooperation with the professionalism of teachers in MTs Pematangsiantar. This research is a quantitative research with correlation research type. This study was conducted in 9 (nine) MTs Pematangsiantar is MTs Negeri, MTsS MESRA, MTsS Khoirotul Islamiyah, MTsS Guppi, MTsS Madani Al Islamiya School, MTsS Ibnu Sina, MTsS Fathul Islamiyah, MTsS YPI, MTsS Al Khairiyah. The population was 88 people and the sample size of the study was 72 people. The results showed; 1) there is a positive and significant relationship between vocational teacher teacher of professionalism of the teacher, if the value of the correlation coefficient is 0.439. 2) There is a positive and significant relationship between the discipline of working with the professionalism of the teacher when the correlation coefficient is 0.502, and 3) a positive and significant relationship between professional money and discipline with the professionalism of teachers with a correlation coefficient of 0.561.